FEATURES AND PROBLEMS IN CUTTING THIN LOGS - Koynov, Daniel (Innovation in Woodworking Industry and Engineering design, 2024)
This study examines some of the most common problems associated with cutting thin logs. Information is summarized from various authors regarding some of the characteristic features and difficulties that arise when cutting this type of timber. Several approaches to processing thin logs with different types of primary woodworking machines are presented. The dimensional and qualitative characteristics of this timber are directly related to both the quantitative and assortment gains, as well as to the deficiencies and defects in the final product. The application of technologies for further processing the obtained bonded materials in the production of engineered wood products (EWP) is associated with high labor costs as well as low quantitative and qualitative yields. Nevertheless, research in this area needs to continue due to the increasingly intensive decrease in the diameter of trees, and consequently a decrease in the average and large construction wood.